2017
DOI: 10.1016/j.arcontrol.2017.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Control sharing in human-robot team interaction

Abstract: The interaction between humans and robot teams is highly relevant in many application domains, for example in collaborative manufacturing, search and rescue, and logistics. It is well-known that humans and robots have complementary capabilities: Humans are excellent in reasoning and planning in unstructured environments, while robots are very good in performing tasks repetitively and precisely. In consequence, one of the key research questions is how to combine human and robot team decision making and task exe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(58 citation statements)
references
References 98 publications
(113 reference statements)
0
58
0
Order By: Relevance
“…How should a contact robot be controlled to provide a stable and appropriate response to a user with unknown dynamics during various activities ranging from sport training, to physical rehabilitation and shared driving [8,9,10]? Specific human-robot interactions have been studied [11,12] but a general framework for interactive control is still missing. It has been suggested that differential game theory (GT) can be used as a framework to describe various interactive behaviors between a robot and its human user [13].…”
Section: Introductionmentioning
confidence: 99%
“…How should a contact robot be controlled to provide a stable and appropriate response to a user with unknown dynamics during various activities ranging from sport training, to physical rehabilitation and shared driving [8,9,10]? Specific human-robot interactions have been studied [11,12] but a general framework for interactive control is still missing. It has been suggested that differential game theory (GT) can be used as a framework to describe various interactive behaviors between a robot and its human user [13].…”
Section: Introductionmentioning
confidence: 99%
“…Adaptive robots and intuitive humans are able to reassign leader/follower roles on-the-fly. With some few exceptions [24,177], recent research assumes that the roles are assigned before task execution. Fig.…”
Section: Definition Of Human-robot Collaborationmentioning
confidence: 99%
“… Collaboration is the joint activity of humans and robots in a shared workspace, with the definite objective to accomplish together a set of given working tasks. It requires typically a coordinated, synchronous activity from all parties [177] where physical contact is also allowed. In any case, collaboration assumes a joint, focused goal-oriented activity from the parties who share their different capabilities, competences and resources.…”
Section: Introductionmentioning
confidence: 99%
“…Predicting and adjusting in real-time to human behaviour and 'communicating' effectively with a human passenger is a task that no machine has mastered yet, possibly because for now at least, humans and machines speak different languages. Humans are excellent in reasoning and planning in unstructured environments, while robots are very good in performing tasks repetitively and precisely (Musić and Hirche, 2017). Also the transition to CAVs will require currently available connectivity to give way to more advanced cooperative features that will facilitate safety and traffic information exchange among vehicles and infrastructure as Raposo et al (2017) suggested.…”
Section: Myth One: Technology Is Already Availablementioning
confidence: 99%